2013
DOI: 10.1590/s0080-62342013000100021
|View full text |Cite
|
Sign up to set email alerts
|

Diagnósticos de enfermagem, fatores relacionados e de risco no pós-operatório de cirurgia bariátrica

Abstract: RESUMOObje vou-se com esta pesquisa iden fi car os principais diagnós cos, fatores relacionados e de risco da classe resposta cardiovascular/pulmonar, propostos pela NAN-DA, versão 2009. Trata-se de estudo de série de caso, descri vo, realizado com vinte pacientes subme dos à cirurgia bariátrica em hospital público de Fortaleza-CE, Brasil. Duas enfermeiras especialistas em unidade de terapia intensiva coletaram os dados por meio de entrevista, exame sico e leitura do prontuário, que foram analisados a par r de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
1
11
0
4
Order By: Relevance
“…However, available studies showed results similar to those of the present study, especially investigations on the ND Acute pain, which is one of the most established for surgical patients (8,(15)(16) . The ND Acute pain (5) was established for 99.3% of patients in our study and have been investigated in several practice scenarios for nurses, who are responsible for diagnosing accurately, intervening appropriately and reassess the results obtained at a later time.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, available studies showed results similar to those of the present study, especially investigations on the ND Acute pain, which is one of the most established for surgical patients (8,(15)(16) . The ND Acute pain (5) was established for 99.3% of patients in our study and have been investigated in several practice scenarios for nurses, who are responsible for diagnosing accurately, intervening appropriately and reassess the results obtained at a later time.…”
Section: Discussionsupporting
confidence: 89%
“…Hypertension was the most frequent comorbidity, followed by osteoarticular disorders. Brazilian studies with similar populations also found a predominance of young females with class III obesity and comorbidities, especially hypertension (8)(9) . It should be highlighted that, in the present study, 85 (59.4%) of patients had a BMI above 40Kg/m², with high levels of morbid obesity.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…(1)(2)(3) On the other hand, the growth of the rates of surgical complications such as dehiscence of the sutures, atelectasis, deep vein thrombosis, or infection is noted. (2)(3)(4)(5)(6) This requires strategies directed towards patient safety, reduction of morbidity and mortality, readmissions and hospital costs.…”
Section: Introductionmentioning
confidence: 99%